Comparison of functional outcome after extended versus super-extended pelvic lymph node dissection during radical prostatectomy in high-risk localized prostate cancer - Heikki Seikkula; Pieter Janssen; Manuela Tutolo; Lorenzo Tosco; Antonino Battaglia; Lisa Moris; Thomas Van den Broeck; Maarten Albersen; Gert De Meerleer; Hendrik Van Poppel; Wouter Everaerts; Steven Joniau (Frontiers Media S.A., 2022)
Background: Urinary continence and erectile function (EF) are best preserved when
meticulous dissection of prostate and nerve sparing technique are used during radical
prostatectomy (RP). However, extent of lymph node dissection (LND) may also adversely
affect functional results.
Objective: To determine whether performing a super-extended LND (seLND) has a
significant effect on recovery of urinary continence and EF after RP.
Design, setting, and participants: All patients who underwent RP from January 2007
until December 2013 were handed questionnaires assessing continence and EF. All
patients in whom at least an extended LND (eLND) was performed were selected. This
search yielded 526 patients. 172 of these patients had filed out 2 or more questionnaires
and were included in our analysis.
Outcome measurements and statistical analysis: All questionnaires were reviewed.
We used Kaplan–Meier analyses and multivariate Cox analysis to assess the difference
in recovery of continence and EF over time for eLND/seLND. Primary endpoints were full
recovery of continence (no loss of urine) and full recovery of EF (successful intercourse
possible). Patients who did not reach the endpoint when the last questionnaire was filled
out were censored at that time. Median follow-up was 12.43 months for continence, and
18.97 months for EF.
results and limitations: Patients undergoing seLND have a lower chance of regaining
both urinary continence [hazard ratio (HR) 0.59, 95% CI 0.39–0.90, p = 0.026] and EF
(HR 0.28, 95% CI 0.13–0.57, p = 0.009). Age at surgery had a significant influence on
both continence and EF in multivariate analysis. Major limitation of the study was that no
formal preoperative assessment of continence and potency was done.
conclusion: Extending the LND template beyond the eLND template may cause at
least a significant delay in recovery of urinary continence and leads to less recovery of EF.